Internet of things, for things, and by things - Chaudhuri, Abhik (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
This book discusses the necessary behavioral attributes for smart living and the policy implications necessary to develop it in order to help citizens be as ready as possible for smart living. It covers the aspect of defects in IoT design and implementation for cyber defense of Smart Services. Includes an indepth discussion of the role of strategic communication in creating safe and secure smart services, with privacy, security and trust. The book aims to help policy makers, engineers, and educators support an ethical, safe, and secure digitally-enhanced environment in which all can live smarter--
Internet "of" Things Internet of Things and Its Potential. The IoT Technology. IoT Architecture. The Philosophy of Information in the IoT. Internet "for" Things Potential Applications of IoT. IoT and Smart Cities. Internet "by" Things Internet as the Foundation for Things: IP v4, IPv6, and Related Concepts. Net Neutrality and Its Impact on IoT. IoT Security, Privacy and GRC Assurance. Managing Shared Risk in Interdependent Systems of Smart Cities. IoT GRC, Standards and Regulations Discussion on Leading Global GRC Frameworks Applicable for IoT Implementations, Regulations (GDPR etc.), Standards ( NIST, ISO, IEEE, IETF, ETSI, etc.) and Role of GRC Audits. Global GRC Frameworks Applicable for IoT Implementations, Regulations, Standards, and Role of GRC Audits. Human Dimension of IoT Developing Policies to Create a Smart "White Box Society" Appendixes.
"A CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa plc."
Includes bibliographical references and index.
CSE
Parama
Keywords: Internet of things; Computer science